Earth's Sea Ice Radiative Effect From 1980 to 2023 - A. Duspayev; M. G. Flanner; A. Riihelä (Geophysical Research Letters)
Abstract Sea ice cools Earth by reducing its absorbed solar energy. We combine radiative transfer modeling with satellite‐derived surface albedo, sea ice, and cloud distributions to quantify the top‐of‐atmosphere sea ice radiative effect (SIRE). Averaged over 1980–2023, Arctic and Antarctic SIREs range from −0.64 to −0.86 W m−2 and −0.85 to −0.98 W m−2, respectively, with different cloud data sets and assumptions of climatological versus annually‐varying clouds. SIRE trends, however, are relatively insensitive to these assumptions. Arctic SIRE has weakened quasi‐linearly at a rate of 0.04–0.05 W m−2 decade−1, implying a 21%–27% reduction in the reflective power of Arctic sea ice since 1980. Antarctic sea ice exhibited a regime change in 2016, resulting in 2016–2023 Antarctic and global SIRE being 0.08–0.12 and 0.22–0.27 W m−2 weaker, respectively, relative to 1980–1988. Global sea ice has therefore lost 13%–15% of its planetary cooling effect since the early/mid 1980s, and the implied global sea ice albedo feedback is 0.24–0.38 W m−2 K−1.